Hubungan Pengetahuan dan Sikap Masyarakat dengan Tindakan Pencegahan Rabies di Wilayah Kerja Puskesmas Molompar - Pinkan F F Pote; Agusteivie A.J Telew; Agustinus R Butarbutar (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Rabies is an acute infection disease of the central nervous sytem caused by a zoonotic virus which spreads through direct contact with wounds or mucosa with the saliva or scratches of infected animals. This type of research is analytical survey research with a cross sectional design (Cross-sectional Study). The sample for this study was 82 namely Mr/Mrs. Who kept dogs and those who did not keep dogs, who where willing to be respondents and fill out the questionnaire. The technique used is probability sampling with the type of sampling, namely simple random sampling. The data analysis used was univariate analysis and bivariate analysis, using the chi-square test. The results of the Chi-Square Test show that there is significant relationship between community knowledge and rabies prevention measures with a P-Value = 0,018 ≤ a (0,05%), there is no significant relationship between community attitudes and rabies prevention actions with the P-Value = 0.293 ≥ a (0.05%), thus it is hoped that health parties can provide education about rabies and vaccinate pets so they can avoid the rabies virus.